MEMBANGUN KOMUNITAS ORANG MUDA KATOLIK PAROKI MARIA DIANGKAT KE SURGA: MENJAWAB TANTANGAN GEN Z DAN ARUS MODERNISASI - Pratiwi, Theresia Dina; Goa, Lorentius (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
The purpose of this study is to understand the unique characteristics of Generation Z (Gen Z) and to formulate a relevant and inclusive categorical pastoral strategy for Catholic Youth (OMK) in Maria Di Angkat Ke Surga Parish, specifically addressing the challenges of individualism and massive modernization. This research employed a descriptive qualitative approach using literature review and pastoral reflection methods, grounded in participant observation and secondary data from Church documents. The key finding indicates that effective pastoral strategy requires harmonizing face-to-face activities (such as choir and social gatherings) with structured digital accompaniment. OMK is susceptible to shallow personal relationships and decreased liturgical participation; thus, an authentic, empowerment-oriented, and participatory community (in line with the principles of Christus Vivit) is crucial. The recommended model emphasizes the formation of small groups for deep sharing and delegating real responsibilities to OMK as active subjects, supported by personal mentoring and the adaptation of digital media as a supplement.